Fermentation Using Providencia stuartii and Salmonella enterica to Produce N-Acetylglucosamine from Shrimp Shells’ Chitin - Halim, Yuniwaty; Chanan Din, Nabilah binti; Soedirga, Lucia C. (FaST : Jurnal Sains dan Teknologi, 2025)
Chitin is a biopolymer that can be extracted from exoskeleton of shrimp shells and other arthropods. One of its derivatives is N-acetylglucosamine that is comprised of glucose and amino acid glutamine. N-acetylglucosamine is known for its health effect, particularly in the treatment of osteoarthritis symptoms. One of the methods to produce N-acetylglucosamine is by fermentation using chitinolytic microorganisms. The aim of this research was to determine the optimum condition (pH, ratio of bacteria, fermentation time, and temperature) for fermentation using the combination of Providencia stuartii and Salmonella enterica to produce N-acetylglucosamine. The research was conducted at different pH (5, 6, 7, 8, 9) and bacterial ratios (3:1, 1:1 and 1:3). Furthermore, the optimum incubation temperature (30, 37, 40oC) and fermentation time (1, 2, 3 and 4 days) were also evaluated. The results showed the optimum condition was achieved at pH 8 with bacterial ratio of 1:1, incubated at 37oC for 3 days.  Under these conditions, N-acetylglucosamine concentration obtained was 87,707.04 ± 906.54 ppm.